(untitled) (Bangladesh Heart Journal, 2024)
A 14 months kid was admitted for routine ventricular septal defect (VSD) closure surgery due to severe pulmonary hypertension (PHT) but day before surgery developed acute severe aortic regurgitation (AR). Per-operative findings highly suggested that this AR due to ruptures fibrous strands of aortic valve. He had no cardiac catheterization before surgery, so its due to turbulent VSD jet affected noncoronary cusp free floating. Refixation with multiple interrupted sutures make near normal anatomy with trival AR at 6 months follow up Echocardiography. Bangladesh Heart Journal 2024; 39(2): 177-178